Value Engineering For Drainage System Planning On Soekarno Hatta Road Malang City - Agus Firmanda, Yocky; Oetomo, Wateno; Wulandari, Esti (Devotion : Journal of Research and Community Service, 2022)
The development of residential areas is very rapid, both in hilly areas and in "water parking" areas. So that puddles occur in several places, where in the past it did not occur. Floods/puddles during the rainy season that occur in the channel area of Jalan Soekarno - Hatta are caused by the capacity of the existing drainage system being no longer able to accommodate rainwater runoff. The aim of this research is Determining alternative drainage structure designs that are more efficient and effective is carried out on Jalan Soekarno - Hatta Malang City using the Value Engineering method and determining cost and time savings after carrying out Value Engineering in the drainage system planning work on Jalan Soekarno - Hatta Malang City. The results of this study is After doing Value Engineering by following the work plan (Job Plan) alternative 2 has been obtained which is efficient because the cost is cheaper (Rp. 15,881,356.00) than other alternatives, and alternative 2 is more effective because time (23 days) is faster than other alternatives . Whereas the initial cost of the U Gutter pair (existing) work on the Drainage System Planning project to Overcome Floods on Jalan Soekarno - Hatta Malang City is Rp. 17,139,144,126.35. While the cost after being in VE, namely alternative 2 Box Culvert Structure, is Rp. 17,014,195,372.72 so that there is a cost savings of Rp. 124,948,753.62 or 0.46%